Characterization and genomic analysis of phage vB_ValR_NF, representing a new viral family prevalent in the Ulva prolifera blooms - Zhang, Xinran; Liang, Yantao; Zheng, Kaiyang; Wang, Ziyue; Dong, Yue; Liu, Yundan; Ren, Linyi; Wang, Hongmin; Han, Ying; McMinn, Andrew; Sung, Yeong Yik; Mok, Wen Jye; et al. (Frontiers in Microbiology, 2023)
Introduction Vibrio is an important bacterial genus containing many pathogenic species. Although more and more Vibrio phages were isolated, the genome, ecology and evolution of Vibrio phages and their roles in bacteriophage therapy, have not been fully revealed. Methods Novel Vibrio phage vB_ValR_NF infecting Vibrio alginolyticus was isolated from the coastal waters of Qingdao during the Ulva prolifera blooms, Characterization and genomic feature of phage vB_ValR_NF has been analysed using phage isolation, sequencing and metagenome method. Results and Discussion Phage vB_ValR_NF has a siphoviral morphology (icosahedral head 114±1 nm in diameter; a tail length of 231±1 nm), a short latent period (30 minutes) and a large burst size (113 virions per cell), and the thermal/pH stability study showed that phage vB_ValR_NF was highly tolerant to a range of pHs (4-12) and temperatures (-20 - 45 °C), respectively. Host range analysis suggests that phage vB_ValR_NF not only has a high inhibitory ability against the host strain V. alginolyticus, but also can infect 7 other Vibrio strains. In addition, the phage vB_ValR_NF has a double-stranded 44, 507 bp DNA genome, with 43.10 % GC content and 75 open reading frames. Three auxiliary metabolic genes associated with aldehyde dehydrogenase, serine/threonine protein phosphatase and calcineurin-like phosphoesterase were predicted, might help the host V. alginolyticus occupy the survival advantage, thus improving the survival chance of phage vB_ValR_NF under harsh conditions. This point can be supported by the higher abundance of phage vB_ValR_NF during the U. prolifera blooms than in other marine environments. Further phylogenetic and genomic analysis shows that the viral group represented by Vibrio phage vB_ValR_NF is different from other well-defined reference viruses, and can be classified into a new family, named Ruirongviridae. In general, as a new marine phage infecting V. alginolyticus, phage vB_ValR_NF provides basic information for further molecular research on phage–host interactions and evolution, and may unravel a novel insight into changes in the community structure of organisms during the U. prolifera blooms. At the same time, its high tolerance to extreme conditions and excellent bactericidal ability will become important reference factors when evaluating the potential of phage vB_ValR_NF in bacteriophage therapy in the future.